Design Of Information System Of Medical Record Web Based Inpatient Public Hospital in South Solo - Akbar, Aidil (LPPM Institut Kesehatan Helvetia, 2018)
Medical record clerk Public Hospital in South Solok still trouble in the process management of inpatient data because it is still using manual systems that haven't computerized. Then needed a medical record information system Web-based inpatient care can help medical record officers in the process of the patient data management. Objectives; To produce a medical record information system Web-based inpatient Public Hospital in South Solok. Method; This system design method using the system development life cycle SDLC (Systems Development Life Cycle) which consists of the stages of planning, analysis, design, implementation, and usage. Results; Produce a medical record information system web-based inpatient public hospital in south solok. which can be used for computerized medical record officers by the management of the medical record in inpatient services unit. Conclusion; The presence of medical record information system Web-based Inpatient Public Hospital in Solok Selatan, can facilitate the attendant medical record medical record data in the management of patient hospitalization, because the system information it generates various reports information medical record of patients required inpatient management for decision making.